IMPROVING STUDENTS' READING SKILL OF DESCRIPTIVE TEXT THROUGH STORY IMPRESSION - Claudia Devi Monalisa; Wardah; Yanti Sri Rezeki (LPPM Universitas PGRI Jombang, 2025)
This study focuses on how story impression can improve students reading skill in descriptive text. The research uses Classroom Action Research that has four steps in its implementation. They are plans, action, observation, and reflection. The subject of the research is the students in seventh grade in SMPN 19 Pontianak which the total number of students is twenty eight. The data was collected by qualitative and quantitative data. The qualitative data was collected by observing the students activity during learning activity, and quantitative data was collected by giving students the test about descriptive text. The writer finished the research in two cycles. In the first cycle, the researcher found that the students’ average scores is 46,42, which it is still below KKM. But in the second cycle, students’ scores achieved into 83,21. From observation results, the writer found that there was an improvement in every meeting. It can be concluded that story impression can improve the students’ comprehension in reading descriptive text.